Graphic Design / A Concise History - Hollis Richard; Thames And Hudson (1996)
From Graphic Art to Design 1890 to 1914, The Avant-Garde and the Origins of Modernism 1914 to 1940, National Tendencies Until 1940, The Designer and the Art Director, Variants of Modernism in Europe, Psychedelia and Protest and New Techniques, New Waves: Electronic Technology.
From Graphic Art to Design 1890 to 1914, The Avant-Garde and the Origins of Modernism 1914 to 1940, National Tendencies Until 1940, The Designer and the Art Director, Variants of Modernism in Europe, Psychedelia and Protest and New Techniques, New Waves: Electronic Technology.